Epoxy hóa dầu hạt hướng dương - Thủy, Nguyễn Thị; Liêm, Nguyễn Thanh; Đức, Vũ Minh (Vietnam Journal of Chemistry, 2016)
Factors such as temperature, stirring speed and time of reaction have very different influences to the epoxidation of sunflower oil. The simultaneous influence of them was studied through titration method oxirane and iodine value. H-NMR spectroscopic analysis results with the appearance of the proton peak in 2.9-3.2 ppm shows the formation of epoxy group. The reaction was carried out at 50 oC or 70 oC and 1000 or 3000 rpm, and mole ratio DB/H2O2 1/1.5. The highest of yield and conversion of the epoxidation are 86.5 % and 92.7 %, respectively. The epoxidized oil possesses 6.76% of oxirane content. Kinetic analysis of the data shows that rate of epoxidation increases with temperature and the value of rate constant (k) is of the order of 10-2 L.mol-1s-1. The kinetic data obtained from this study were compared with from epoxidation of rubber seed oil, cottonseed oil, mahua oil, palm olein methyl ester with peroxy acid. Keywords. Vegetable oil epoxidation, sunflower oil, tungsten, kinetic analysis